A functional genomics approach to investigate the differentiation of iPSCs into lung epithelium at air‐liquid interface. Issue 17 (21st July 2020) - Kerschner, Jenny L.; Paranjapye, Alekh; Yin, Shiyi; Skander, Dannielle L.; Bebek, Gurkan; Leir, Shih‐Hsing; Harris, Ann
Abstract: The availability of robust protocols to differentiate induced pluripotent stem cells (iPSCs) into many human cell lineages has transformed research into the origins of human disease. The efficacy of differentiating iPSCs into specific cellular models is influenced by many factors including both intrinsic and extrinsic features. Among the most challenging models is the generation of human bronchial epithelium at air‐liquid interface (HBE‐ALI), which is the gold standard for many studies of respiratory diseases including cystic fibrosis. Here, we perform open chromatin mapping by ATAC‐seq and transcriptomics by RNA‐seq in parallel, to define the functional genomics of key stages of the iPSC to HBE‐ALI differentiation. Within open chromatin peaks, the overrepresented motifs include the architectural protein CTCF at all stages, while motifs for the FOXA pioneer and GATA factor families are seen more often at early stages, and those regulating key airway epithelial functions, such as EHF, are limited to later stages. The RNA‐seq data illustrate dynamic pathways during the iPSC to HBE‐ALI differentiation, and also the marked functional divergence of different iPSC lines at the ALI stages of differentiation. Moreover, a comparison of iPSC‐derived and lung donor‐derived HBE‐ALI cultures reveals substantial differences between these models.